Supporting self-care of type 2 diabetes in Malaysia - Saidi, Sanisah (IIUM Press, International Islamic University Malaysia, 2017)
This book is describing the management of type 2 diabetes in Malaysia. A marked increase in type 2 diabetes and associated morbidity and mortality rate over the last 10 years has been recorded in Malaysia. Ineffective diabetes management and a lack of self-care practice among type 2 diabetic patients have been identified as the major reasons for this problem. Research in other countries has highlighted a range of factors influencing effective self-care of type 2 diabetes including patients’ perspectives of diabetes, sociocultural issues, religious beliefs and support from healthcare. This book will provide information on how the patients with type 2 diabetes are currently being supported within the primary and secondary healthcare settings in urban areas in Malaysia in enhancing their self-care practice. It also provides information on how healthcare professionals who involved in the diabetes management perceived their roles and support that they gave to the patients. This book is intended to increase understanding of the healthcare professionals on the issues around the diabetes management and self-care support for patients with type 2 diabetes.